2016
DOI: 10.1016/j.cell.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation-Dependent IFN-γR Partitioning in Lipid and Actin Nanodomains Is Critical for JAK Activation

Abstract: Understanding how membrane nanoscale organization controls transmembrane receptors signaling activity remains a challenge. We studied interferon-γ receptor (IFN-γR) signaling in fibroblasts from homozygous patients with a T168N mutation in IFNGR2. By adding a neo-N-glycan on IFN-γR2 subunit, this mutation blocks IFN-γ activity by unknown mechanisms. We show that the lateral diffusion of IFN-γR2 is confined by sphingolipid/cholesterol nanodomains. In contrast, the IFN-γR2 T168N mutant diffusion is confined by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
113
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 112 publications
(120 citation statements)
references
References 40 publications
4
113
0
3
Order By: Relevance
“…In the second step, JAK1/2 activation induces a second conformational change that allows STAT1 to associate with the IFN␥-IFNGR complex. In turn, JAK1 and JAK2 phosphorylate the transcription factor STAT1 (pSTAT1) forming a homodimer that translocates to the nucleus (9). At this moment, the released IFNGRs associated with the cortical-actin network and prepared for alternative regulation via receptor trafficking and endocytosis.…”
Section: Canonical Ifn␥-signaling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second step, JAK1/2 activation induces a second conformational change that allows STAT1 to associate with the IFN␥-IFNGR complex. In turn, JAK1 and JAK2 phosphorylate the transcription factor STAT1 (pSTAT1) forming a homodimer that translocates to the nucleus (9). At this moment, the released IFNGRs associated with the cortical-actin network and prepared for alternative regulation via receptor trafficking and endocytosis.…”
Section: Canonical Ifn␥-signaling Pathwaysmentioning
confidence: 99%
“…The IFNGR is composed of two distinct chains, the high affinity IFNGR1 (␣) and a low affinity IFNGR2 (␤) (8). The identification of a glycosylation-deficient mutant residue in the IFNGR1 detailed two key steps preceding initiation of IFN␥ signaling (9). In the first step, IFN␥ binding induces the receptors to undergo a conformational change in lipid nano-domains, whereby the box 1 domains on the IFNGRs are brought into proximity of each other allowing recruitment of two JAKs, JAK1 and JAK2, to the IFNGR1 and IFNGR2 chains, respectively.…”
Section: Canonical Ifn␥-signaling Pathwaysmentioning
confidence: 99%
“…For example, during the activation of immune cells, well-defined fractions of immune receptors are thought to form receptor clusters through transient trapping of their intracellular domains. 29,30 In turn, certain lipids such as 1,2-dioleoyl- sn -glycero-3-phosphoethanolamine (DOPE) and the transferrin receptor have been shown to undergo hindered hop diffusion within the dense cortical actin network beneath the cell membrane. 4,2527 Conventional sFCS recordings theoretically contain all the kinetic information on such hindered diffusion of fluorescent particles, including hop and trapped diffusion modes within the observed probe ensemble.…”
mentioning
confidence: 99%
“…Normally, IFN-γ can stimulate the immune system, interfere with virus replication, and help to eradicate pathogens [22]. A study showed IFN-γ could induce the production of IL-12 in vivo to inhibit the secretion of IL-14 by T-helper 2 (Th2) cells, and further promote T-helper 1 (Th1) polarization [23].…”
Section: Discussionmentioning
confidence: 99%